A Digital Revolution in Education Using Tech Tools and Smart Devices - Paramasivam, C. (International Journal of Psychosocial Rehabilitation, 2020)
Technology is the beacon of light in the world of education and bewitches almost everyone towards it include learners, teachers and content creators. Education is no exception to miss the tide of technological change which navigates the learning world with a sea of innovations and ideas. In the current scenario, a kid even before joining the primary school can operate the modern gadgets with more ease than the older generations. Smart Phone is one such gadget which provides mobile telephony, entertainment, sports, news, games and numerous multi-purpose applications for the young and elderly. Today’s tech-savvy generation adapts quickly to newer methods of teaching and learning modes faster than their predecessors. This paper discusses the recent innovations in education and modes of learning, tech tools and digital platforms that make learning simpler and effective for both the teaching and student fraternity.